ANALISIS KEBAKARAN HUTAN DAN LAHAN DI SAMARINDA (Analysis of Forest and Land Fire in Samarinda) - Edwardus Iwantri Goma; Djurlin Lampang; Fathan Purwadi; Inayah Inayah; Lasdin Sagala; Riska Riska; Deviani Deviani (Universitas Muhammadiyah Gorontalo, 2021)
The phenomenon of forest and land fires is also an annual problem that is often faced in East Kalimantan Province, especially in the Samarinda area. The purpose of this study was to determine the causes of forest and land fires, and to identify follow-up actions to reduce the risk of forest and land fires in Samarinda. Data collection techniques were carried out using documentation techniques which were carried out in three stages, namely 1) Editing; 2) Organizing; and 3) Finding: The data analysis technique used in this research is to use the data analysis method of the Miles and Huberman model which is carried out in three stages, namely 1) Data reduction; 2) Display data and; 3) Drawing conclusions. The results showed that forest and land fires that occurred in several areas of the city of Samarinda were caused by two main factors, namely human activities and weather factors. The follow-up for risk reduction is early warning and steps to increase preparedness in the community.